Strategi Pengembangan Desa Wisata Berbasis Masyarakat di Nagari Mandeh - Iftita Rahmi Efendi Efendi; Vikri; Sherlyna; Popi Marseli; Fadillah Nisa Caniago; Yuliana (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Community-Based Tourism Village Development Strategy in Nagari Mandeh. Mandeh Nagari tourism village is a tourist village that has beautiful natural tourism potential. This study aims to formulate a community-based development strategy for the Mandeh Nagari Tourism Village (CBT), which is a tool for sustainable tourism development. The research method used is mixed (mix method). Qualitative data through observation, interviews, documentation and Focus Group Discussion (FGD) were then analyzed by data reduction, data presentation and conclusion. Quantitative data was collected by distributing questionnaires and then analyzed descriptively. The results showed that the Mandeh Nagari tourism village could be developed with CBT (Community Based Tourism), such as re-activating tourism awareness groups and providing assistance to tourism activities in the Mandeh Nagari tourism village.